2018
DOI: 10.1128/aem.00813-18
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Supply Chain with Microbial Travelers: a Farm-to-Retail Microbial Simulation and Visualization Framework

Abstract: Fresh produce supply chains present variable and diverse conditions that are relevant to food quality and safety because they may favor microbial growth and survival following contamination. This study presents development of a simulation and visualization framework to model microbial dynamics on fresh produce moving through post-harvest supply chain processes. The Post-harvest Supply Chain with Microbial Travelers (PSCMT) tool provides a modular process modeling approach and graphical user interface to visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Mercier and Uysal [73] trained a neural network using a heat transfer model to estimate temperature accurately so that food quality along the SC could be ensured. Zoellner et al [74] simulated a model for the microbial dynamics of fresh products using a postharvest SC using the microbial travelers (PSCMT) tool. The tomato SC from Mexico to the USA was examined and a PSCMT model was proposed.…”
Section: Food-related Problems/postharvest Losses Along the Ffvscmentioning
confidence: 99%
“…Mercier and Uysal [73] trained a neural network using a heat transfer model to estimate temperature accurately so that food quality along the SC could be ensured. Zoellner et al [74] simulated a model for the microbial dynamics of fresh products using a postharvest SC using the microbial travelers (PSCMT) tool. The tomato SC from Mexico to the USA was examined and a PSCMT model was proposed.…”
Section: Food-related Problems/postharvest Losses Along the Ffvscmentioning
confidence: 99%
“…Postharvest supply chain with microbial travelers: A farm-to-retail microbial simulation and visualization framework [178] 2018 Dynamic model and graphical user interface: A solution for the distribution process of regional products [179] 2020…”
Section: ) Intermediariesmentioning
confidence: 99%
“…In addition to user interfaces for specific target stakeholders, some works provided user interfaces for system administrators or did not explicitly state target users [160]- [162], [164], [165], [167], [170], [178]. Interestingly, neither processors nor distributors were discussed as targets of benefits or source of challenges in the review papers.…”
Section: ) Customersmentioning
confidence: 99%
“…Additionally, post‐harvest handling in the packing house and during distribution is intricate practices that can alter the microbial load. Zoellner et al (2018) modelled and identified parameters and processes including chlorinated wash, cross‐contamination and time after packaging as some of the most influential in the determination of the microbial loads in tomato post‐harvest procedures from Mexico to the USA.…”
Section: Sweetcorn Post‐harvest Treatments For Improved Quality: the Solutionsmentioning
confidence: 99%